Biosynthetic potential of sesquiterpene synthases: Alternative products of tobacco 5-epi-aristolochene synthase - O’Maille, Paul E. (2006)
Nicotiana tabacum (tobacco) 5-epi-aristolochene synthase (TEAS) serves as an useful model for understanding the enzyme mechanisms of sesquiterpene biosynthesis. Despite extensive bio-chemical and structural characterization of TEAS, a more detailed analysis of the reaction product spectrum is lacking. This study reports the discovery and quantification of several alternative sesquiterpene products generated by recombinant TEAS in the single-vial GC–MS assay. The combined use of chiral and non-polar stationary phases for gas chromatography separations proved critical for resolving the numerous sesquiterpene products of TEAS for mass spectral analysis and identification. Co-injection studies with available authentic standards from both synthetic and natural sources further corroborated the assignment of several compounds, resulting in an annotated reaction mechanism accounting for their biosynthesis. Moreover, a previously undocumented farnesyl trans–cis isomerization pathway was observed.